2018
DOI: 10.1186/s42358-018-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a health education program on cytokines and cortisol levels in fibromyalgia patients: a randomized controlled trial

Abstract: Background: Fibromyalgia (FM) is a syndrome characterized by widespread chronic pain associated to other symptoms, such as: fatigue, anxiety, depression and sleep disorders. Health education programs (HEP) have emerged as good non-pharmacological strategies to treat it. However, it is still not clear if the benefits are only subjective, or it has also objective impacts on immune and or neuroendocrine systems. Methods: Fifty-eight fibromyalgia women were randomly allocated in experimental group (n = 27) or cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
(64 reference statements)
0
21
0
Order By: Relevance
“…Cortisol measurement protocols (in urine or blood) and pain tolerance or threshold tests were conducted using different instruments and protocols. This disparity might explain why Torgrimson-Ojerio et al [40] noted significant reductions in cortisol in their FM group while others report significant reductions in the control group [34]. Variation in pain was described in the study by Geiss et al, who used the pressure pain threshold method [33], while Pernambuco et al, Riva et al, and Stehlik et al, measured pain more subjectively though the fibromyalgia impact questionnaire (FIQ) and visual analogue scale (VAS), respectively [34,35,38].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Cortisol measurement protocols (in urine or blood) and pain tolerance or threshold tests were conducted using different instruments and protocols. This disparity might explain why Torgrimson-Ojerio et al [40] noted significant reductions in cortisol in their FM group while others report significant reductions in the control group [34]. Variation in pain was described in the study by Geiss et al, who used the pressure pain threshold method [33], while Pernambuco et al, Riva et al, and Stehlik et al, measured pain more subjectively though the fibromyalgia impact questionnaire (FIQ) and visual analogue scale (VAS), respectively [34,35,38].…”
Section: Discussionmentioning
confidence: 92%
“…Several independent studies for this review were selected according to descriptive statistics and effect sizes reported for the effects of several predictive variables on cortisol levels. In two of these studies, significant medium size effects were observed [31,38], while in three, effects were both significant and large [18,34,40].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations